Electrocrystallization of UO2 on nanoporous WO3/W electrode in LiCl-KCl melts. (20th December 2021) - Li, Haiming; Liu, Rugeng; Han, Wei; Wang, Wenjuan; Zhang, Yongqiang; Sun, Yang; Zhang, Meng; Li, Mei
Highlights: The electrochemical reduction of UO 2 2 + was studied using nanoporous WO3 /W electrode. j 0 of UO 2 + / UO 2 pair was measured on nanoporous WO3 /W and W electrodes by Tafel technique. The nucleation mechanism of UO2 was probed on nanoporous WO3 /W substrate by CA. The difference of UO2 morphology formed on W and WO3 /W electrodes was discussed. Abstract: To investigate the effect of cathode materials on the formation of UO2 in LiCl-KCl-UO2 Cl2 melts, the electrochemical formation and nucleation mechanisms of UO2 were investigated on WO3 /W nanoporous electrode fabricated by anodization at applied voltage of 40 V in KF-H2 SO4 solution at 298 K. Cyclic voltammetry, square wave voltammetry and chronopotentiometry results indicated that the reduction of UO 2 2 + to UO2 on nanoporous WO3 /W electrode was found to be via two-step reactions: (1) UO 2 2 + + e − ↔ UO 2 + ; (2) UO 2 + + e − ↔ UO 2 . Meanwhile, the disproportionation reaction 2 UO 2 + ↔ UO 2 2 + + UO 2 was also observed. Furthermore, the exchange current density ( j 0 ) of UO 2 + / UO 2 pair was measured on various electrodes by Tafel technique. The value of j 0 on W electrode is larger than that on nanoporous WO3 /W electrode, and the lower exchange current density could result in the increase of nucleus critical radius. The nucleation mechanism of UO2 on WO3 /W substrate was probed to be progressive nucleation with three-dimensional growth. Constant potential electrolysis was conducted at -1.0 V to compare the difference of deposit morphology on W and WO3 /W electrodes. The characterized results of deposits using SEM, XRD and TEM indicated that orthorhombic UO2 structure was formed on WO3 /W electrode, while the dendritic morphology UO2 on W electrode. Graphical abstract: Image, graphical abstract